PENYELESAIAN SENGKETA PENANAMAN MODAL MELALUI ARBITRASE INTERNASIONAL (STUDI KASUS PENCABUTAN IZIN KUASA PERTAMBANGAN CHURCHILL MINING OLEH PEMERINTAH DAERAH KABUPATEN KUTAI TIMUR) - SOPHIE DINDA AULIA BRAHMANA; BUDIMAN GINTING; MAHMUL SIREGAR (Universitas Sumatera Utara, 2013)
Investment dispute between states and national of other states are settled through international arbitration (ICSID). ICSID (International Centre for Settlement of Investment Disputes) is an autonomous international institution Because of the provisions of this, British Company Churchill Mining who have a Investment dispute with Indonesian Government filed a lawsuit against the government of Indonesia at the International Centre for Settlement of Investment Disputes (ICSID). Writing method used to compile this paper is the normative legal research or library research, by collecting material from books, magazines, papers, internet, legislation and other scholarly writings which closely related with the intent and purpose of the preparation of this paper. The results of this paper it can be concluded that, the foreign investors who have an Investment Dispute with other state like Churchill Mining Plc can settle their Investment Dispute through ICSID. This provision is based on Indonesian Law No. 25 of 2007 about investment and Indonesian Law No. 5 of 1968 concerning the approval of the Convention on the Settlement of Investment Disputes between States and Nationals of Other States. Kata Kunci: Penyelesaian Sengketa, Arbitrase Internasional, ICSID, Churchill Mining